ANALISIS PENGARUH KUALITAS WEBSITE, LINGKUNGAN DAN DAYA TARIK KONTEN TERHADAP IMPULSIVE BUYING PADA WEBSITE OLX MELALUI PERILAKU HEDONIK - Septiani, Shelomita Elisabeth; Sugiarto, Sugiarto; Yoestini, Yoestini (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2016)
Along with era’s development, there is a shift which consumers prefer to buy via online shopping rather than going straight to the mall or come to the store to buy something. This research aims to analyze the effect of website’s quality toward hedonic behavior, to analyze the effect of environment toward hedonic behavior, to analyze the effect of content attractiveness toward hedonic behavior, to analyze the effect of hedonic behavior toward impulsive buying.Sample in this research is 97 respondents that are shopping on the OLX website. The technique of data analysis is using SPSS, with validity and realibility test, the classic assumption test and multiple regression.The result of this research shows that the Quality of the Website doesn’t has positive effect toward hedonic behavior, Environment have positive effect toward Hedonic Behavior, the Attractiveness of Content have positive and significant effect toward Hedonic Behavior, Hedonic Behavior have a positive effect toward Impulsive Buying.